Resin raw material composition
Patent Information
- Application Number
- JP2024214096
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-08-21
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-11
AI Technical Summary
【0008】 本発明によれば、従来に比べて機械特性に極めて優れたポリエステルイミド樹脂が製造できる樹脂原料用組成物を、提供することが可能となる。さらに、特定の不純物が機械特性に影響を及ぼすことを見出したことから、その特定の不純物を低減した樹脂原料用組成物から、より強靭な機械特性を有するポリエステルイミド樹脂を製造することが可能となる。
Smart Images

Figure 2025032249000001 
Figure 2025032249000002 
Figure 2025032249000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin raw material composition used for producing a resin having excellent mechanical properties. [Background technology]
[0002] Polyimides not only have excellent heat resistance, but also chemical resistance, radiation resistance, electrical insulation, and excellent mechanical properties, and therefore are widely used in various electronic devices such as flexible printed circuit (FPC) boards, TAB (Tape Automated Bonding) substrates, protective films for semiconductor elements, and interlayer insulating films for integrated circuits. In addition to these properties, polyimides have become increasingly important in recent years due to their simplicity of production method, extremely high film purity, and ease of property improvement using various available monomers. The compound represented by the following formula (a), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride) (hereinafter, may be referred to as "compound a"), is a useful compound as a raw material for polyesterimide resins that have a high glass transition temperature, a low coefficient of linear thermal expansion equivalent to that of metal foil, an extremely low water absorption rate, a high elastic modulus, sufficient toughness, and sufficient adhesion to metal foil (e.g., Patent Documents 1 and 2). [ka] [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-001394 A [Patent Document 2] International Publication No. 2014 / 046180 Summary of the Invention [Problem to be solved by the invention]
[0004] When a polyesterimide resin is produced using compound a as a raw material, the mechanical properties of the resulting resin may vary significantly even if the resin is produced by the same production method. Therefore, there has been a demand for a resin raw material composition that can produce a polyesterimide resin having stronger mechanical properties.
[0005] Conventionally, nothing has been known about impurities contained in compound a as by-products in the synthesis reaction process and purification process, and furthermore, the influence of these impurities on the production of a polyesterimide resin, and these have not been studied at all. The present invention has been made in light of the above-mentioned circumstances, and an object of the present invention is to provide a resin raw material composition that makes it possible to produce a polyesterimide resin having extremely excellent mechanical properties compared to conventional compositions. [Means for solving the problem]
[0006] As a result of intensive research aimed at solving the above-mentioned problems, the present inventors have found that certain impurities contained in 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride) affect the mechanical properties of the resulting polyesterimide resin, and have completed the present invention.
[0007] The present invention is as follows. 1. A resin raw material composition comprising, as component A, a compound represented by the following formula (a), and as component B, a compound represented by the following formula (b), in the following composition ratio: [Composition ratio]: When measured by gel permeation chromatography using a differential refractometer as a detector, component A is 99.0 area % or more and 99.99 area % or less, and component B is 0.005 area % or more and 0.4 area % or less, based on the total amount of all detected components. [ka] [ka] (wherein R represents a hydrogen atom or R1-CO- (wherein R1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms)). 2. A method for producing a polyesterimide, comprising: a step (i) of reacting a composition containing, as component A, a compound represented by the following formula (a), and as component B, a compound represented by the following formula (b), in the composition ratio described below, with a diamine to obtain a polyesterimide precursor, and then a step (ii) of imidizing the same. [Composition ratio]: When measured by gel permeation chromatography using a differential refractometer as a detector, component A is 99.0 area % or more and 99.99 area % or less, and component B is 0.005 area % or more and 0.4 area % or less, based on the total amount of all detected components. [ka] [ka] (wherein R represents a hydrogen atom or R1-CO- (wherein R1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms)). Effect of the Invention
[0008] According to the present invention, it is possible to provide a resin raw material composition capable of producing a polyesterimide resin having extremely superior mechanical properties compared to conventional compositions. Furthermore, since it has been found that specific impurities affect the mechanical properties, it is possible to produce a polyesterimide resin having stronger mechanical properties from a resin raw material composition in which the specific impurities are reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. <Component A> The resin raw material composition of the present invention contains, as component A, a compound a represented by the following formula (a) "2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(trimellitate anhydride)" as a main component. [ka]
[0010] The content of component A in the resin raw material composition of the present invention is 99.0 area % or more and 99.99 area % or less based on the total amount of all components detected by gel permeation chromatography using a differential refractometer as a detector. The lower limit is preferably 99.1 area % or more, and more preferably 99.3 area % or more.
[0011] <Component B> The resin raw material composition of the present invention contains, as component B, a compound represented by the following formula (b) in a range of 0.005 area % or more and 0.4 area % or less based on the total amount of all components detected by measurement by gel permeation chromatography using a differential refractometer as a detector. The upper limit is preferably 0.35 area % or less, more preferably 0.3 area % or less, further preferably 0.2 area % or less, and particularly preferably 0.15 area % or less. In addition, the lower limit may be preferably 0.01 area % or more from the viewpoint of suppressing a decrease in the yield of the target component A when repeated purification is performed. A polyesterimide resin obtained by using a resin raw material composition containing more than 0.4 area % of the compound represented by the following formula (b) as measured above has significantly reduced mechanical properties. [ka] (wherein R represents a hydrogen atom or R1-CO- (wherein R1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms)).
[0012] A specific example of component B in the resin raw material composition of the present invention is the following compound b1, in which "R" in the above formula (b) is a hydrogen atom. [ka] The compound b1 is a compound that is generated as a reaction intermediate when compound a is synthesized by the "acid halide method", which is one of the methods for producing a resin raw material composition of the present invention, as described below. The reaction formula for generating compound b1 by the "acid halide method" is shown below. [ka]
[0013] Furthermore, a specific example of component B in the resin raw material composition of the present invention is the following compound b2, in which "R" in the above formula (b) is R1-CO- and "R1" is an alkyl group having 1 carbon atom. [ka] The compound b2 can be produced by the process for producing a resin raw material composition of the present invention, "Elastomer" which will be described later. This compound is produced as a reaction intermediate when synthesizing compound A by the ester exchange method. The reaction scheme for producing compound b2 by the “ester exchange method” is shown below. [ka] In addition, the compound b2 can be obtained by the above-mentioned "acid halide method" by converting anhydrous acetic acid into acetic acid in the post-reaction treatment step. When an acid is used, the compound b1 produced is also the compound produced by reaction with acetic anhydride. The reaction formula is shown below. [ka]
[0014] <Production method 1: "Acid halide method"> The "acid halide method", which is one of the methods for producing a resin raw material composition of the present invention, will be described below. The "acid halide method" is a method for producing the resin raw material composition of the present invention containing compound a as a main component by reacting 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with trimellitic anhydride halide, as shown in the following reaction formula. [ka]
[0015] The trimellitic anhydride halide used in the above-mentioned "acid halide method" includes trimellitic anhydride chloride (corresponding to the compound in the above-mentioned reaction formula), trimellitic anhydride bromide, trimellitic anhydride iodide, and trimellitic anhydride fluoride. Among these trimellitic anhydride halides, trimellitic anhydride chloride is preferably used because it is inexpensive and easily available. The amount of the trimellitic anhydride halide used is usually 2 to 3 moles, and preferably 2.1 to 2.5 moles, per mole of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol. In the above-mentioned "acid halide method", hydrogen halide is generated by the reaction of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with anhydrous trimellitic acid halide, and a base is used to capture this. Such a base is not particularly limited, but organic tertiary amines such as pyridine, triethylamine, and N,N-dimethylaniline, epoxy compounds such as propylene oxide, and inorganic bases such as potassium carbonate and sodium hydroxide can be used. Among them, pyridine is preferably used from the viewpoints of separation operation after the reaction, cost, harmfulness, and the like.
[0016] In the above-mentioned "acid halide method", the reaction is started by mixing a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol in the same solvent with trimellitic anhydride dissolved in a solvent. At this time, a base such as pyridine is contained in the solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, which is the solution to be mixed. In addition, contrary to the above-mentioned mixing method, when a solution of trimellitic anhydride is mixed in a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, by-products are more likely to be generated than in the former mixing method. Therefore, the former mixing method, that is, a method of mixing a solution of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol dissolved in the same solvent with a solution of trimellitic anhydride dissolved in a solvent, is preferred. The molar ratio of the starting materials and base used in the reaction, 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol / trimellitic anhydride halide / base, is preferably within the range of 1.0 / 2.1 to 2.5 / 3.0 to 5.0. The above solutions are mixed at a low temperature. The temperature in the reaction system is preferably in the range of −10 to 10° C., more preferably in the range of −5 to 7° C., and particularly preferably in the range of 0 to 5° C. There is no restriction on the time required for mixing, but 2 to 4 hours is preferable.
[0017] Stirring immediately after the completion of mixing 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol and trimellitic anhydride halide (hereinafter, sometimes referred to as "post-stirring 1") continues to be performed at a low temperature, preferably at a temperature in the reaction system in the range of -10 to 10°C, more preferably at a temperature in the range of -5 to 7°C, and particularly preferably at a temperature in the range of 0 to 5°C. In this temperature range, "post-stirring 1" is preferably performed within about 5 hours, more preferably 2 to 3 hours. After this "post-stirring 1", in order to promote the reaction, stirring (hereinafter sometimes referred to as "post-stirring 2") can be continued at a temperature higher than that of "post-stirring 1" to complete the reaction. "Post-stirring 2" is preferably carried out at a reaction system temperature in the range of 50 to 75°C, more preferably in the range of 55 to 70°C, and particularly preferably in the range of 60 to 65°C. "Post-stirring 2" is preferably carried out within such a temperature range for approximately 5 hours, and more preferably for 2 to 3 hours.
[0018] The solvent that can be used in the above-mentioned "acid halide method" is not particularly limited as long as it does not inhibit the reaction, and examples thereof include aprotic solvents such as tetrahydrofuran, 1,4-dioxane, picoline, pyridine, acetone, chloroform, toluene, xylene, dichloromethane, chloroform, 1,2-dichloroethane, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-diethylacetamide, N,N-dimethylformamide, hexamethylphosphoramide, dimethylsulfoxide, γ-butyrolactone, γ-valerolactone, 1,3-dimethyl-2-imidazolidinone, 1,2-dimethoxyethane-bis(2-methoxyethyl)ether, and acetonitrile. These solvents may be used alone or in combination of two or more. Among these, tetrahydrofuran, γ-butyrolactone, γ-valerolactone, acetonitrile, etc. are preferably used from the viewpoint of quickly carrying out the reaction and suppressing the remaining of the compound b1, which is a reaction intermediate.
[0019] <Production method 2: "Transesterification method"> The "transesterification method", which is one of the methods for producing a resin raw material composition of the present invention, will be described below. This "transesterification method" is a method for producing the resin raw material composition of the present invention containing compound a as a main component by reacting a dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with trimellitic anhydride, as shown in the following reaction formula. [ka] (wherein R1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
[0020] Specific examples of the dicarboxylic acid ester of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol used in the above-mentioned "transesterification method" include 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(acetate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(propionate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(butyrate), 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(benzoate), and 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol-bis(naphthoate). These dicarboxylates of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol can be produced by a conventional method, for example, a method of reacting 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol with a carboxylic anhydride or a carboxylic acid halide. The amount of trimellitic anhydride used in the above "ester exchange method" is usually 2 or more moles, preferably 2 to 10 moles, and particularly preferably 2.6 to 3.4 moles, per mole of the dicarboxylate of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol. The reaction temperature of the above "ester exchange reaction" is usually in the range of 100 to 300°C, preferably in the range of 150 to 250°C, and particularly preferably in the range of 200 to 230°C.
[0021] In the above-mentioned "transesterification method", it is preferable to use a base as a catalyst in the reaction. Specific examples of these bases include inorganic alkali metal compounds such as alkali metal hydroxides, carbonates, and hydrogen carbonate compounds, and organic alkali metal compounds such as alkali metal alcohols, phenols, and salts with organic carboxylic acids. Specific examples of the base include sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, lithium acetate, sodium acetate, and potassium acetate. The amount of these bases used is in the range of 0.001 to 10 mol %, preferably 0.005 to 5 mol %, relative to 1 mol of the dicarboxylate of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol.
[0022] In the above-mentioned "transesterification method", it is preferable to use a reaction solvent in the reaction for reasons such as improved operability and reaction rate during industrial production. The solvent that can be used is not particularly limited as long as it does not distill from the reaction vessel at the above-mentioned reaction temperature and is inactive in the transesterification reaction. Specific examples of the solvent include aromatic hydrocarbon ether solvents such as alkylaryl ethers such as phenetole and butylphenyl ether, diaryl ethers such as diphenyl ether and di-p-tolyl ether, aromatic hydrocarbon solvents such as biphenyl and terphenyl, alkyl-substituted naphthalenes such as diisopropylnaphthalene, aliphatic hydrocarbons such as decalin and kerosene, polyalkylene glycol ethers such as tetraethylene glycol dimethyl ether and diethylene glycol dibutyl ether, and organic solvents such as Therm-S series (manufactured by Nippon Steel Chemical Co., Ltd.), KSK-OIL series (manufactured by Soken Chemical Co., Ltd.), or Neo SK-OIL series (manufactured by Soken Chemical Co., Ltd.). When these solvents are used, the amount used is usually in the range of 1 to 10 parts by weight, preferably 2 to 3 parts by weight, per part by weight of the dicarboxylate of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol.
[0023] <Refining> The resin raw material composition of the present invention can usually be obtained by purifying the reaction product obtained by the above-mentioned reaction so that the content of the compound represented by formula (b) as component B falls within a specific range. The purification method can be a known method, but is preferably performed by crystallization and reslurry (suspending a solid in a solvent). In order to adjust the content of component B to a specific amount, it is more preferable to repeat these operations not only once but multiple times. The solvent that can be used for crystallization and reslurry is not particularly limited as long as it is a solvent that is inert to component A, and specific examples include acetic anhydride, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, tetrahydrofuran, methyl isobutyl ether, methyl isopropyl ether, toluene, xylene, ethylbenzene, γ-butyrolactone, γ-valerolactone, acetonitrile, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, etc. Among them, acetic anhydride, cyclohexanone, γ-butyrolactone, etc. are preferred. Although the crystallization conditions vary depending on the solvent used and cannot be generally stated, for example, when γ-butyrolactone is used, the amount of the solvent used is in the range of 5 to 50 parts by weight, more preferably in the range of 10 to 30 parts by weight, and particularly preferably in the range of 1 to 20 parts by weight, per 1 part by weight of the total amount of the composition containing Component A, Component B, and other impurities to be purified. The temperature during dissolution is in the range of 100 to 200°C, more preferably in the range of 110 to 180°C, even more preferably in the range of 110 to 160°C, and particularly preferably in the range of 120 to 140°C. The cooling temperature is in the range of 0°C to 50°C, more preferably in the range of 10 to 40°C, and even more preferably in the range of 15 to 30°C. The conditions of the reslurry method vary depending on the solvent used and cannot be generally stated, but for example, when γ-butyrolactone is used, the amount of the solvent used is preferably in the range of 2 to 20 parts by weight, more preferably in the range of 2 to 12 parts by weight, and even more preferably in the range of 4 to 8 parts by weight, per 1 part by weight of the total amount of the composition containing component A, component B, and other impurities to be purified. The treatment temperature is preferably in the range of 100 to 200°C, more preferably in the range of 110 to 180°C, even more preferably in the range of 110 to 160°C, and particularly preferably in the range of 120 to 140°C. The reslurry treatment is preferably carried out for about 0.5 to 3 hours. When using other solvents, various conditions can be appropriately changed taking into consideration the boiling point of the solvent, the solubility of component A, component B, other impurities, and the composition containing them to be purified, and the like. Furthermore, before crystallization by purification procedures such as crystallization and reslurrying, a solution containing a composition containing components A and B and other impurities can be filtered to filter out inorganic salts or washed with water to obtain a high-purity product with further reduced metal components such as inorganic salts. In this case, even if some or all of the acid anhydride groups of components A and B are ring-opened to form carboxylic acids upon contact with water, they can be returned to carboxylic acid anhydrides by heat treatment or reaction with an acid anhydride such as acetic anhydride. The purified product obtained by these purification steps may contain the solvent used, so it is preferable to remove the solvent and dry it. The method for removing the solvent is not particularly limited, but examples include a method in which the solvent is distilled off by heating under normal pressure or reduced pressure.
[0024] <Polyesterimide obtained using the resin raw material composition of the present invention> A polyesterimide can be produced by reacting the resin raw material composition of the present invention with a diamine in step (i) to obtain a polyesterimide precursor (polyamic acid), and then imidizing the same in step (ii).
[0025] <(i) Step of Obtaining Polyesterimide Precursor (Polyamic Acid)> The step of obtaining a polyesterimide precursor involves reacting the resin raw material composition of the present invention with a diamine. As a specific method, for example, in a reaction vessel, first, the diamine is dissolved in a polymerization solvent, and the resin raw material composition of the present invention, which is an acid dianhydride in a substantially equimolar amount to the diamine, is gradually added to the solution to carry out the reaction. The temperature at this time is in the range of 0 to 100°C, preferably in the range of 5 to 80°C, more preferably in the range of 10 to 60°C, even more preferably in the range of 15 to 40°C, and particularly preferably in the range of 20 to 30°C. In this case, the raw material monomer concentration is usually in the range of 5 to 50% by weight. By carrying out the polymerization in such a monomer concentration range, a polyesterimide precursor having a uniform and high degree of polymerization can be obtained. If the degree of polymerization of the polyesterimide precursor increases too much and the polymerization solution becomes difficult to stir, it can be appropriately diluted with the same solvent. The diamine that can be used is not particularly limited, but aromatic diamines and aliphatic diamines can be used. Specific examples of aromatic diamines include p-phenylenediamine, 3,4'-diaminodiphenyl ether, 4-aminophenyl-4'-aminobenzoate, benzidine, 3,3'-dihydroxybenzidine, 2,2'-bis(trifluoromethyl)benzidine (TFMB), 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane, 2,2-bis(4-aminophenyl)hexafluoropropane, and 2,2-bis(4-aminophenyl)fluorene, with 2,2'-bis(trifluoromethyl)benzidine (TFMB) being particularly preferred. Specific examples of aliphatic diamines include 4,4'-methylenebis(cyclohexylamine), 1,4-cyclohexanebis(methylamine), 2,2-bis(4-aminocyclohexyl)propane, 2,2-bis(4-aminocyclohexyl)hexafluoropropane, trans-1,4-diaminocyclohexane, 1,4-tetramethylenediamine, 1,5-pentamethylenediamine, and 1,6-hexamethylenediamine. As the polymerization solvent that can be used, any solvent can be used as long as it dissolves the raw material monomers, the polyesterimide precursor produced, and the imidized polyesterimide and does not interfere with the reaction. For example, amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone, cyclic ester solvents such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, and α-methyl-γ-butyrolactone, carbonate solvents such as ethylene carbonate and propylene carbonate, glycol solvents such as triethylene glycol, phenol solvents such as m-cresol, p-cresol, 3-chlorophenol, and 4-chlorophenol, acetophenone, 1,3-dimethyl-2-imidazolidinone, sulfolane, and dimethyl sulfoxide can be used. Among these, aprotic solvents such as amide solvents, cyclic ester solvents, and carbonate solvents are preferred, and specifically, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, dimethylsulfoxide, etc. are preferred. Furthermore, it is preferred to use these solvents that have been dehydrated in advance. When polymerizing a polyesterimide precursor, an aromatic or aliphatic tetracarboxylic acid dianhydride other than the resin raw material composition of the present invention, which is a tetracarboxylic acid dianhydride, can be used in combination as a copolymerization component. By using the resin raw material composition of the present invention, it is possible to obtain a polyesterimide precursor having a higher intrinsic viscosity than when using conventional raw materials.
[0026] <(ii) Step of imidizing the polyesterimide precursor> Next, the step of imidizing the obtained polyesterimide precursor to obtain a polyesterimide will be described. The polyesterimide precursor can be imidized by known methods such as a thermal imidization method in which the polyesterimide precursor is thermally dehydrated and cyclized, a chemical imidization method using a dehydrating agent, etc. Among these, the chemical imidization method, which does not require high-temperature heat treatment and can perform imidization under mild conditions, is preferred. In the thermal imidization method, for example, the reaction solution in the step of obtaining the polyesterimide precursor described above is mixed with an azeotropic agent with water, such as toluene or xylene, and reacted while removing by-product water from the system by heating, thereby performing imidization. The reaction temperature at that time is preferably heated to a temperature at which water is distilled from the system or higher, for example, the azeotropic point or higher or 100°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher. Heating at 150°C or higher is not preferable because the solvent, etc., may become colored, and the colored components may cause coloring of the film. As another method, the polyesterimide precursor solution obtained by polymerization is cast on a substrate such as glass and dried to form a precursor film. After that, the substrate may be heated at normal pressure or in vacuum in the range of 200 to 400°C to perform imidization. In the chemical imidization method, for example, the polyesterimide precursor solution is adjusted to an appropriate solution viscosity for easy stirring with the same solvent as that used in polymerization, and a dehydration ring-closing agent (chemical imidization agent) consisting of an organic acid anhydride and a basic catalyst is mixed while stirring with a stirrer to cause an imidization reaction. The temperature at this time is in the range of 0 to 100°C, preferably in the range of 5 to 80°C, more preferably in the range of 10 to 60°C, further preferably in the range of 15 to 40°C, and particularly preferably in the range of 20 to 30°C. The organic acid anhydride that can be used in this case is not particularly limited, but examples thereof include acetic anhydride, propionic anhydride, etc. Acetic anhydride is preferably used because of ease of handling and purification of the reagent. The basic catalyst is not particularly limited, but pyridine, triethylamine, quinoline, etc. can be used, with pyridine being preferred from the viewpoint of ease of handling and separation of the reagent. The amount of organic acid anhydride in the chemical imidization agent is in the range of 1 to 10 times the theoretical dehydration amount of the polyesterimide precursor by mole, and the amount of basic catalyst is in the range of 0.1 to 2 times the amount of organic acid anhydride by mole. Since the reaction solution after the chemical imidization contains by-products such as a chemical imidization agent and a carboxylic acid, it is necessary to remove these and purify the polyesterimide. A known method can be used for purification. For example, the simplest method is to drop the imidized reaction solution into a large amount of poor solvent (e.g., an alcohol solvent such as methanol or ethanol, or an aliphatic hydrocarbon solvent such as hexane) while stirring to precipitate the polyesterimide, and then recover the polyesterimide powder. If the solid content concentration of the polyimide contained in the reaction solution dropped into the poor solvent is too high, the precipitated polyimide may become lumps, and impurities may remain in the coarse particles, or it may take a long time to redissolve the obtained polyimide powder in the solvent. On the other hand, if the concentration is too low, a large amount of poor solvent is required, which may increase the environmental load due to waste solvent treatment and increase the production cost. Therefore, a solvent such as the polymerization solvent may be added to the liquid after the polyesterimide is precipitated. Then, if necessary, the powder is repeatedly washed until the by-products are removed, and the powder to which the solvent is attached is dried under reduced pressure to obtain a polyesterimide powder. By applying the method for producing polyesterimide of the present invention, it is possible to obtain polyesterimide having a higher intrinsic viscosity than when conventional raw materials are used. Furthermore, it is possible to obtain polyesterimide having significantly improved breaking strength, average elongation at break, and maximum elongation in the tensile strength test results when formed into a film.
[0027] <Preparation of Polyesterimide Solution> The resulting polyesterimide can be dissolved in an organic solvent to form a solution. The organic solvent can be appropriately selected depending on the application of the solution and the processing conditions. In the case of continuous coating for a long period of time, the organic solvent in the polyesterimide solution may absorb moisture from the air, causing precipitation of the polyesterimide. Therefore, it is preferable to use a low hygroscopic solvent such as triethylene glycol dimethyl ether, γ-butyrolactone, or cyclopentanone. The solid content of the solution is not particularly limited and can be appropriately selected depending on the application of the solution. For example, when the solution is made into a film, the solid content is preferably 5% by weight or more, although it depends on the molecular weight of the polyesterimide, the production method, and the thickness of the film to be produced.
[0028] <Production of Polyesterimide Film> The polyesterimide solution thus obtained can be used to mold the polyesterimide into a film. A known method can be used as the manufacturing method, and for example, a polyesterimide film can be manufactured by applying the polyesterimide solution onto a support such as a glass substrate using a doctor blade or the like, and then drying the applied solution. Furthermore, in order to remove residual strain, a heat treatment can be performed in an inert gas atmosphere or in vacuum at a temperature in the range of 150 to 300°C. EXAMPLES
[0029] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. 1. Gel Permeation Chromatography Equipment: Tosoh Corporation high-speed GPC equipment HLC-8320GPC Columns: 1 TSKgel guardcolum HXL-L, 2 TSKgel G2000HXL, 1 TSKgel G3000HXL, TSKgel G400 Flow rate: Pump Sam. 1.0ml / min, 1 / 3 of Ref. Sam. Mobile phase: Tetrahydrofuran Column temperature: constant at 40℃ Detector: Differential refractometer (RI) The RI detector detects the difference in refractive index between the solution on the sample side and the eluent on the reference side, and the refractive index of the solution correlates with the weight concentration of the solution. Sample concentration: 30mg / 50ml (tetrahydrofuran solution) Injection volume: 100μl 2. Time-of-flight mass spectrometry (TOF-MS analysis) Equipment: Bruker TOF-MS MicroTOFSII Ion source: APCI / direct probe Target ion species: Cations
[0030] 3.Intrinsic viscosity The reduced viscosity of a 0.5 wt % polyimide precursor solution and a polyimide solution was measured at 30° C. using an Ostwald viscometer (manufactured by Shibata Scientific, SIBATA 026300-1, inner diameter about 0.5 mm). This value was regarded as the intrinsic viscosity. 4. Breaking strength and elongation at break Using a universal material testing machine Model 5569, load cell: 100N (manufactured by Instro Japan Co., Ltd.), tensile tests (test speed: 100mm / min) were performed on polyimide film test pieces (JIS K6251 dumbbell type 6), and the breaking elongation (%) was calculated from the breaking strength (MPa) and the elongation at which the film broke (number of tests: 5). The higher the breaking elongation, the higher the toughness of the film. The breaking strength was determined from the stress at the time of breaking.
[0031] <Synthesis Example 1> A resin raw material composition was produced in order to prepare the resin raw material compositions of the following Comparative Examples 1 and 2. The detailed operation method is as follows. A four-neck flask equipped with a thermometer, a stirrer, and a cooling tube was charged with 53.0 g (0.25 mol) of trimellitic anhydride chloride and 197.4 g of tetrahydrofuran, and the container was replaced with nitrogen while stirring and dissolving, and cooled to below 5 ° C. Then, a preparation solution in which 40.0 g (0.15 mol) of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, 250.0 g of tetrahydrofuran, and 23.4 g (0.30 mol) of pyridine were dissolved was dropped at a constant rate over 2 hours while maintaining the temperature in the flask at 5 ° C. or less. After the dropwise addition, the mixture was stirred at 2 to 8 ° C. for 24 hours. Then, water was added at room temperature, and after stirring for 2 hours, the internal temperature was raised to 40 ° C. and reacted for 6 hours. Then, the mixture was cooled to below 10 ° C. and a large amount of water was added, and a white precipitate was formed. Then, the white precipitate was filtered and dried in vacuum at 60 ° C. to obtain 62.5 g of product. The product and acetic anhydride were then charged into a four-neck flask and reacted at 100°C for 2 hours, then cooled to room temperature while stirring for 24 hours, resulting in the formation of a white precipitate. The precipitate was filtered and washed with γ-butyrolactone. It was then dried under reduced pressure at 120°C for 1 hour and at 150°C for 1 hour. The precipitate was further washed by holding it at 100°C for 1 hour using γ-butyrolactone, cooled, filtered, and dried under reduced pressure at 150°C for 2 hours. The white solid thus obtained was subjected to gel permeation chromatography (GPC) RI analysis and TOF-MS analysis. As a result, the obtained resin raw material composition was a composition containing 87.7 area % of compound a as component A of the present invention, and 10.4 area % of the total of compounds b1 and b2 as component B of the present invention. In addition, the TOF-MS analysis detected the molecular weight of the exact mass of compound b1 (E / Z=444) and the molecular weight of the exact mass of compound b2 (E / Z=486), confirming that the compounds had the chemical structural formulas (b1) and (b2) in the following chemical formula. [ka]
[0032] <Example 1> The resin raw material composition of the present invention was produced by the following detailed operation method. In a four-neck flask equipped with a thermometer, a stirrer, and a cooling tube, 411.8g (1.96mol) of trimellitic anhydride chloride and 1213.0g of tetrahydrofuran were charged, and the container was replaced with nitrogen while stirring and dissolving, and cooled to below 5°C. Then, a preparation solution in which 229.8g (0.85mol) of 2,2',3,3',5,5'-hexamethyl-biphenyl-4,4'-diol, 1545.0g of tetrahydrofuran, and 336.2g (4.25mol) of pyridine were dissolved was dropped at a constant rate over 2 hours while maintaining the temperature in the flask at 5°C or less. After the dropwise addition, stirring was performed for 2 hours at 5°C or less (post-stirring 1). Then, the temperature was raised to 65°C and stirring was performed for 3 hours (post-stirring 2). After the reaction was completed, the mixture was cooled to 40°C while stirring, 200.0 g of water was added, and the mixture was kept at 40°C for 14 hours. The mixture was then cooled to 25°C and the precipitate formed was filtered off. Then, the product and acetic anhydride were charged into a four-neck flask, and the mixture was kept at 100°C for 2 hours, cooled to 25°C, and the precipitate formed was filtered off. The precipitate separated by filtration was further washed in a slurry state at 120°C using γ-butyrolactone, and filtered at 25°C. The precipitate separated by filtration was further washed in a slurry state at 100°C using cyclohexanone, and filtered at 25°C. The precipitate separated by filtration was heated to 100°C under reduced pressure and dried. The white solid thus obtained was subjected to gel permeation chromatography (GPC) RI analysis, which revealed that the composition contained 99.4 area % of compound a as component A and 0.1 area % of the total of compound b1 and compound b2 as component B of the present invention, and was a resin raw material composition of the present invention.
[0033] (Polymerization of polyimide precursor) 1.284g (4.01mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) was dissolved in 33.784g of dehydrated N,N'-dimethylacetamide (DMAc). 2.469g (3.97mmol) of the resin raw material composition of Example 1 was slowly added thereto, and the mixture was stirred at room temperature for 72 hours to obtain a polyamic acid, which is a polyimide precursor (solid content concentration: 10.0% by weight). The intrinsic viscosity of the obtained polyamic acid was 5.01dL / g.
[0034] (Chemical imidization reaction) The obtained polyamic acid was diluted with dehydrated dimethylacetamide to a solid content concentration of 6.5% by weight. A mixed solution of 24.69 mmol of acetic anhydride and 12.35 mmol of pyridine was slowly dropped into the solution at room temperature while stirring, and the mixture was further stirred for 24 hours after the dropwise addition. The obtained polyimide solution was slowly dropped into a large amount of methanol. Dimethylacetamide was further added to precipitate fibrous polyimide, which was then filtered off. The obtained white precipitate was washed with methanol and dried under vacuum at 60°C.
[0035] (Preparation of polyimide solution and formation of polyimide film) The polyimide powder was redissolved in cyclopentanone at room temperature to prepare a 5.1 wt% homogeneous solution. This polyimide solution was cast onto a glass substrate and dried in a hot air dryer at 60°C for 2 hours. The substrate was then heat-treated in vacuum at 250°C for 1 hour and allowed to cool to room temperature, after which the film was peeled off from the glass substrate. This polyimide film was once again heat-treated in vacuum at 250°C for 10 minutes to remove residual strain. The resulting polyimide film was nearly colorless and transparent. The mechanical properties of this polyimide film (thickness: 20 μm) were measured, and the results are shown in Table 1 below.
[0036] <Example 2> In order to evaluate the effect of the content of component B, the resin raw material composition of the present invention obtained in Example 1 and the resin raw material composition obtained in the above Synthesis Example 1 were mixed by weight so that the content of component B was 0.3 area % to prepare a composition (at this time, compound a was 99.3 area %). When the polymerization of polyimide precursor was carried out in the same manner as in Example 1, the intrinsic viscosity was 4.39 dL / g at 52 hours and 4.46 dL / g at 72 hours. Subsequently, a chemical imidization reaction was carried out in the same manner as in Example 1, and a polyimide film was prepared and mechanical properties were measured. The results are shown in Table 1 below.
[0037] <Comparative Example 1> In the same manner as in Example 2, the components were mixed by weight so that the content of component B was 1.0 area % to prepare a composition (at this time, compound a was 98.4 area %). When the polymerization of the polyimide precursor was carried out in the same manner as in Example 1, the intrinsic viscosity was 3.29 dL / g after 52 hours and 3.30 dL / g after 72 hours. Subsequently, a chemical imidization reaction was carried out in the same manner as in Example 1, and a polyimide film was produced and its mechanical properties were measured. The results are shown in Table 1 below.
[0038] <Comparative Example 2> In the same manner as in Example 2, the components were mixed so that the content of component B was 0.5 area % to prepare a composition (at this time, compound A was 98.9 area %). When the polymerization of the polyimide precursor was carried out in the same manner as in Example 1, the intrinsic viscosity was 4.24 dL / g after 52 hours and 4.26 dL / g after 72 hours. Subsequently, a chemical imidization reaction was carried out in the same manner as in Example 1, and a polyimide film was prepared and its mechanical properties were measured. The results are shown in Table 1 below.
[0039] <Comparative Example 3> The manufacturing method described in "Synthesis Example 1" of the above Patent Document 2 was retested, and the recrystallized product obtained through the "purification" process was subjected to gel permeation chromatography (GPC) RI analysis. As a result, the composition contained 96.4 area % of compound a as component A of the present invention, and 1.8 area % of the total of compound b1 and compound b2 as component B of the present invention. In addition, the chemical structures of compound b1 and compound b2 were also confirmed in the same manner as in Example 1. The "polyamic acid intrinsic viscosity," "polyimide acid intrinsic viscosity," and mechanical properties of polyimide films described in "Example 1" (paragraphs 0065-0067) of the above Patent Document 2 are transcribed below in Table 1 with the symbol "*." These mechanical properties cannot be simply compared with the above Examples 1 and 2 and Comparative Examples 1 and 2 because the film thickness and test conditions are different, but are listed as reference values.
[0040] [Table 1]
[0041] The results in Table 1 reveal that when the resin raw material compositions of Examples 1 and 2 containing specific amounts of Component A and Component B of the present invention are used, the intrinsic viscosity of the resulting polyamic acid and polyimide is increased, and the average breaking strength, maximum breaking strength, average breaking elongation, and maximum breaking elongation in the tensile strength test results of the resulting polyimide film are all significantly improved, as compared with the resin raw material compositions of Comparative Examples 1 to 3 containing a small amount of Component A, the main component, and a large amount of Component B, an impurity.
Claims
1. A resin raw material composition comprising, as component A, a compound represented by the following formula (a), and as component B, a compound represented by the following formula (b), in the following composition ratio: [Composition ratio]: Component A is 99.0 area % or more and 99.99 area % or less, and component B is 0.005 area % or more and 0.4 area % or less, based on the total amount of all detected components, as measured by gel permeation chromatography using a differential refractometer as a detector. 【Chemistry 1】 【Chemistry 2】 (In the formula, R is a hydrogen atom or R 1 -CO- (wherein R 1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
2. A method for producing a polyesterimide, comprising: a step (i) of reacting a composition containing, as component A, a compound represented by the following formula (a) and, as component B, a compound represented by the following formula (b), in the compositional ratio described below, with a diamine to obtain a polyesterimide precursor; and a step (ii) of imidizing the polyesterimide precursor. [Composition ratio]: Component A is 99.0 area % or more and 99.99 area % or less, and component B is 0.005 area % or more and 0.4 area % or less, based on the total amount of all detected components, as measured by gel permeation chromatography using a differential refractometer as a detector. 【Chemistry 3】 【Chemistry 4】 (In the formula, R is a hydrogen atom or R 1 -CO- (wherein R 1 represents an alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 12 carbon atoms).
Citation Information
Patent Citations
New ester group-containing tetracarboxylic acid dianhydride, new polyester imide precursor to be derived therefrom, and polyester imide
JP2014001394A
Polyimide and molded body thereof
WO2014046180A1